Specific energy consumption reduction during pulsed electrochemical oxidation of phenol using graphite electrodes. Issue 2 (June 2016) - Mu'azu, Nuhu Dalhat; Al-Yahya, Muhammad; Al-Haj-Ali, Ahmad M.; Abdel-Magid, Isam Mohammed
Abstract: Electrochemical oxidation (ECO) processes are energy intense systems as they mostly run under continuous constant current supply mode. This study investigated the feasibility of energy consumption reduction during oxidation of phenol using graphite electrodes under pulsed electrochemical oxidation (PECO) process. Response surface methodology (RSM) was employed to model and optimize the influences of pulsed duty cycle, PDC, (0.5–0.9), current density, CD, (5–15 mA cm −2 ) and initial phenol concentration (100–500 mg/L) on the removal efficiencies of phenol and total organic carbon (TOC) and their associated specific energy consumption (SEC). The TOC and phenol removals and their respective SEC increase with increasing CD and PDC and decreasing with initial phenol concentration. The RSM models developed explained the experimental data quite well (0.994 < R 2  < 0.998). The optimal conditions obtained which targeted most efficient energy utilization with concomitant high removal efficacies for both phenol and TOC removal were achieved at higher levels of all the investigated parameters yielding phenol and TOC removal of 59.41 and 33.08% at SEC of 111 kWh/kg-phenol and 205 kWh/kg-TOC, respectively. At lower initial phenol concentration, better phenol oxidation is achievable by increasing the PDC and the CD, though at the expense of significant increase in SEC. Due to inherent low oxidative activity of graphite anode, longer electrolysis time to improve performance of PECO of phenol would undermine the feasibility of SEC reduction when graphite anode is employed.